2014
DOI: 10.1186/s12935-014-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stem-like side population cells in a recurrent nasopharyngeal carcinoma cell line

Abstract: BackgroundSide population (SP) assay identifies cells with dye/drug extrusion ability, a characteristic of stem cells. Here, we determined if SP cells exist in a verified cell line originating from recurrent nasopharyngeal carcinoma (NPC) and a xenograft established from recurrent metastatic NPC. These cells were evaluated for stem-like properties via functional assays as well as for tumourigenicity.MethodsWe used Hoechst 33342 to identify the SP from non-SP (NSP) cells in HK1 NPC cell line and xeno-284 NPC xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Nasopharyngeal CSCs have been evaluated by analyzing the number of side population (SP) cells, which appear as a dimly stained subgroup by extruding the Hoechst 33342 dye [12][13][14], as well as the expressions of octamer-binding transcription factor 3/4 (Oct3/4), sexdetermining region Y-box 2 (Sox2), c-myc, and Nanog [14]. Sufficient evidence has demonstrated that Oct3/4, Sox2, c-myc, and Nanog function as reprograming factors which can efficiently transform terminally differentiated cells into induced pluripotent stem cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal CSCs have been evaluated by analyzing the number of side population (SP) cells, which appear as a dimly stained subgroup by extruding the Hoechst 33342 dye [12][13][14], as well as the expressions of octamer-binding transcription factor 3/4 (Oct3/4), sexdetermining region Y-box 2 (Sox2), c-myc, and Nanog [14]. Sufficient evidence has demonstrated that Oct3/4, Sox2, c-myc, and Nanog function as reprograming factors which can efficiently transform terminally differentiated cells into induced pluripotent stem cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…This phenotype has been isolated from several primary tumors and cancer cell lines, including those of the lung, esophagus, nasopharynx, and oral cavity (8)(9)(10). Furthermore, ABCG2 expression has been found in solid tumors of hepatocellular, lung, pancreas, and head and neck squamous carcinomas (HNSCC) (8)(9)(10). ABCG2 plays a critical role in the maintenance of the stem cell phenotype and multidrug resistance of cancer cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that the ABCG2-positive side population cells with the ability to exclude Hoechst 33342 and the possession of cancer stem-like properties may play an important role in oral carcinogenesis (9). Increasing evidence suggests ABCG2 is a marker in CSC and plays a central role in tumorigenesis (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). In addition, it was previously observed that HK1 contained a subset of cells termed side population (SP) cells, which were enriched with CSC-associated genes (101). A separate study identified certain CSC genes to be responsible for the formation of spheroids in HK1 (97).…”
Section: Npc 3d Spheroidsmentioning
confidence: 99%